Application of Optical Coherence Tomography Angiography in True and Pseudo-Optic Disc Swelling - Kaveh Abri Aghdam; Ali Aghajani; Amin Zand; Samira Chaibakhsh; Pasha Anvari; Fatemeh Zahra Ijadi; Khalil Ghasemi Falavarjani (Journal of Ophthalmology)
Purpose. We evaluated the optic disc microvasculature in healthy subjects and patients with optic nerve head drusen (ONHD), active papilledema, and acute nonarteritic anterior ischemic optic neuropathy (NAION) using optical coherence tomography angiography (OCTA). Methods. This prospective, comparative case series included sixteen eyes with ONHD, thirty-one eyes with active papilledema, sixteen eyes with acute NAION, and thirty-two healthy eyes. The Optovue AngioVue OCT and OCTA Imaging System recorded peripapillary retinal nerve fiber layer (RNFL) thickness and vessel density maps from the radial peripapillary capillary (RPC) slab. Results. Average RNFL thicknesses were greater in eyes with ONHD, papilledema, and NAION compared to control eyes (all Ps<0.001), but this parameter did not differ among patient groups. The mean peripapillary vessel density did not differ between the ONHD and control groups (P=1.000), nor between the NAION and papilledema groups (P=0.216). However, this value in the ONHD and control groups was significantly higher than in the NAION and papilledema groups (all Ps<0.05). Conclusion. RPC density is influenced during the progression of conditions such as ONHD, papilledema, and NAION. Although a decrease in vessel density values has been observed in cases of true disc edema, further research is necessary to assess the potential of OCTA in differentiating between true and pseudo-optic disc edema.